The ASEME methodology. (29th April 2022) - Spanoudakis, Nikolaos I.; Moraitis, Pavlos
In this paper, we present a complete view of an agent-oriented software engineering methodology called agent systems engineering methodology ( ASEME ). Several parts of the methodology concerning different aspects of the whole development process have already been published in the past in several papers. However, our goal in this paper is to provide a global view on the methodology by providing information about the agent (and multi-agent systems) development process along with recent works concerning the tools that we have developed in order to facilitate the use of ASEME by agent systems developers. We also provide some information on the different practical applications that we have developed using ASEME and which prove that ASEME is very well suited for the development of real world applications.